(untitled) (Al-Academy, 2023)
Reality is an inexhaustible resource for filmmakers, and since political, economic, religious and other topics are the main drivers of lived reality, filmmakers and those involved in this field realize the importance of cinematic art and the great ability that can inspire and influence the audience, because marginalization includes an ideological goal for cinema. Americanism and whoever stands behind it, it has become necessary to confront this concept and examine its dimensions and representations. From here, the tagged research was launched (Ideological marginalization of the image of Arabs in American cinema?). The research included the research problem, the need for it, the importance of the research and its objectives. The second chapter included two topics, the first topic (ideology, beginning and extension), in which the researcher dealt with (ideology, term and concept), but in the second topic, it was entitled (construction of false consciousness in American cinema). The third chapter included: (the research methodology), (the research community), and (the research tool) and then the sample analysis. As for the fourth chapter (results and conclusions), in which the results of the research were reviewed, including (the maker of the work relied on the topic of marginalization on the dialogue indicating the structure of the verb), then the conclusions, proposals and recommendations, and the research concluded with a list of sources and references